1. ## Using the Quadratic Formula???

I am having difficulty with the following problem because I do not know how to use the quadratic formula. Can anyone explain step by step on how to do the following problem using the quadratic formula?

x^2/(2.00-x)(1.00-x) = .64

Any input will be greatly appreciated. Thank you.

2. Originally Posted by confused20
I am having difficulty with the following problem because I do not know how to use the quadratic formula. Can anyone explain step by step on how to do the following problem using the quadratic formula?

x^2/(2.00-x)(1.00-x) = .64

Any input will be greatly appreciated. Thank you.
$\frac{x^2}{(2 - x)(1 - x)} = 0.64$

$x^2 = 0.64(2 - x)(1 - x)$

$x^2 = 0.64(2 - 3x + x^2)$

$x^2 = 1.28 - 1.92x + 0.64x^2$

$0.36x^2 + 1.92x - 1.28 = 0$

Now a = 0.36, b = 1.92, and c = -1.28

-Dan

3. ## How did you arrive at .36x^2?

Thank you a great deal for your response. Can you please tell me how you arrived at .36x^2? I am having difficulty understanding what operation you did to arrive at that figure. Thanks once again for your replay.

4. Here it is along with the extra step:

$\frac{x^2}{(2 - x)(1 - x)} = 0.64$

$x^2 = 0.64(2 - x)(1 - x)$

$x^2 = 0.64(2 - 3x + x^2)$

$x^2 = 1.28 - 1.92x + 0.64x^2$
=====================================
$x^2 - 0.64x^2 + 1.92x - 1.28 = 0$
=====================================

$0.36x^2 + 1.92x - 1.28 = 0$

Now a = 0.36, b = 1.92, and c = -1.28

-Dan

5. Thank you once again for your replay. To get .36x^2 from .64x^2 do you just subtract by .28? If so, what is the reason that you subtract by .28? Thank you again for all your help.

6. Originally Posted by confused20
Thank you once again for your replay. To get .36x^2 from .64x^2 do you just subtract by .28? If so, what is the reason that you subtract by .28? Thank you again for all your help.
Look at the coefficients oftthe $x^2$ terms. They are 1 and 0.64 respectively. Then 1 - 0.64 = 0.36.

-Dan